2017
DOI: 10.1024/0301-1526/a000656
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism following surgical treatment of superficial venous incompetence

Abstract: Summary:Background: The invasive management of varicose veins has a known risk of post-operative deep venous thrombosis and subsequent pulmonary embolism. The aim of this study was to evaluate absolute and relative risk of venous thromboembolism (VTE) following commonly used varicose vein procedures. Patients and methods: A retrospective analysis of secondary data using Hospital Episode Statistics database was performed for all varicose vein procedures performed between 2003 and 2013 and all readmissions for V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 12 publications
1
16
0
5
Order By: Relevance
“…However, prospective studies which systematically detected DVT by means of duplex ultrasound showed that the true incidence might be 5-10 times higher than expected on a clinical basis. 5,14,15 There is also a recognised increased risk of DVT in primary care patients who have varicose veins regardless of surgery. 16 Also in the Republic of Ireland there is no universal health record number meaning that patients who are diagnosed with a VTE in a different hospital from where they had their venous procedure may not be notified to the surgeon who performed it, particularly if the event is diagnosed some time after the procedure.…”
Section: Dvt Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, prospective studies which systematically detected DVT by means of duplex ultrasound showed that the true incidence might be 5-10 times higher than expected on a clinical basis. 5,14,15 There is also a recognised increased risk of DVT in primary care patients who have varicose veins regardless of surgery. 16 Also in the Republic of Ireland there is no universal health record number meaning that patients who are diagnosed with a VTE in a different hospital from where they had their venous procedure may not be notified to the surgeon who performed it, particularly if the event is diagnosed some time after the procedure.…”
Section: Dvt Ratesmentioning
confidence: 99%
“…Although the DVT may have been present before this, it is clear that formal imaging at for example one week post-op may miss some cases of DVT. 14 The other issue is the difference between endovenous heat-induced thrombosis (EHIT) and formal DVT. EHIT can be divided into four categories, the fourth of which is often classified as a DVT; therefore, some would view EHIT and DVT as both on the same continuum.…”
Section: Dvt Ratesmentioning
confidence: 99%
“…In der Literatur wird ein postoperatives Thrombembolierisiko von ca. 0,5 % beschrieben [7]. Das deckt sich mit unseren Erfahrungen.…”
Section: Postoperative Thromboseunclassified
“…Barker et al [7] beschreibt in den ersten 30 postinterventionellen Tagen jedoch eine niedrigere Inzidenz thrombembolischer Ereignisse nach Schaumsklerosierung und ein insgesamt (nach 90 Tagen) ähnlich hohes Risiko für thrombembolische Ereignisse nach der operativen Sanierung, der endovenösen Therapie und einer Schaumsklerosierung.…”
Section: Postoperative Thromboseunclassified
“…For patients at high risk, the main focus of the Advice is the duration of prophylaxis, because evidence from the time-incidence of post-procedure VTE supports longer administration of anticoagulants than has hitherto been practiced. 6,7 These include patients with multiple risk factors or a single dominant risk factor (such as personal history of unprovoked VTE). In the new environment of COVID, this will also include patients who have venous interventions who have had or who are at high risk of acquiring COVID, with its intrinsic tendency to thrombotic problems.…”
mentioning
confidence: 99%